Efficacy Trial of a Selective Prevention Program Targeting both Eating Disorders and Obesity among Female College Students: 1- and 2-Year Follow-Up Effects - Stice, Eric (2012)
OBJECTIVE: Evaluate the effects of a prevention program targeting both eating disorders and obesity at 1- and 2-year follow-ups. METHOD: Female college students at risk for these outcomes because of body image concerns (N = 398) were randomized to the Healthy Weight 2 group-based 4-hour prevention program, which promotes lasting healthy improvements to dietary intake and physical activity and nutrition science health behavior change principles, or an educational brochure control condition. RESULTS: Intervention participants showed significantly less body dissatisfaction and eating disorder symptoms and lower eating disorder onset through 2-year follow-up versus controls, but the former two effects were small. There were no main effects for BMI, depressive symptoms, dieting, caloric intake, physical activity, or obesity onset. Moderator analyses revealed stronger eating disorder symptom effects for youth with initially elevated symptoms and lower pressure to be thin, stronger BMI effects for youth with initially elevated symptoms and BMI scores, and weaker eating disorder symptom effects for youth with initially elevated pressure to be thin. CONCLUSIONS: The 60% reduction in eating disorder onset over the 2-year follow-up was clinically significant and a novel effect for a prevention program, but the main effects on continuous outcomes were small, suggesting that adding nutrition science principles weakened the intervention efficacy. Effects on both eating disorder symptoms and BMI were greater for those with elevated eating disorder symptoms and BMI at pretest, implying that it might be useful to target these individuals in future trials.